Is Work Motivation Important? The Role of Work Motivation to See the Consistency of Grit Influence on Individual Work Performance: English - Syukri Santoso; Siti Aisyah; Suryani Hardjo (Yayasan Ilomata, 2026)
This study aims to analyze the contribution of work motivation on the influence of grit on individual work performance. This research conducted quantitative non-experimental. The sample in this study amounted to 60 police personnel. Data were collected using three scales adopted from previous research. The results direct effect indicate it has been observed that grit exerts a significant influence on individual work performance, with an estimated value of 0.503. This influence is categorized as